Activation of biosynthetic gene clusters by the global transcriptional regulator TRI6 in Fusarium graminearum. Issue 4 (7th August 2020) - Shostak, Kristina; Bonner, Christopher; Sproule, Amanda; Thapa, Indira; Shields, Samuel W. J.; Blackwell, Barbara; Vierula, John; Overy, David; Subramaniam, Rajagopal
Abstract: In F. graminearum, the transcription factor TRI6 positively regulates the trichothecene biosynthetic gene cluster (BGC) leading to the production of the secondary metabolite 15‐acetyl deoxynivalenol. Secondary metabolites are not essential for survival, instead, they enable the pathogen to successfully infect its host. F. graminearum has the potential to produce a diverse array of secondary metabolites (SMs). However, given high functional specificity and energetic cost, most of these clusters remain silent, unless the organism is subjected to an environment conducive to SM production. Alternatively, secondary metabolite gene clusters (SMCs) can be activated by genetically manipulating their activators or repressors. In this study, a combination of transcriptomic and metabolomics analyses with a deletion and overexpressor mutants of TRI6 was used to establish the role of TRI6 in the regulation of several BGCs in F. graminearum . Evidence for direct and indirect regulation of BGCs by TRI6 was obtained by chromatin immunoprecipitation and yeast two‐hybrid experiments. The results showed that the trichothecene genes are under direct control, while the gramillin gene cluster is indirectly controlled by TRI6 through its interaction with the pathway‐specific transcription factor GRA2. Abstract : The activation of biosynthetic gene clusters in fungi is limited by ecological considerations. The biological function of the majority of the metabolites originating from these clusters is unknown. Hence, alterations in growth conditions, epigenetic manipulation of the genome, and ectopic expression of transcriptional regulators are used to expose the "cryptic" clusters to synthesize metabolites. This study used nutrient conditions and ectopic expression of regulators to reveal expression and biosynthesis of novel metabolites.